Pemikiran Ibn Taimiyah Tentang Regulasi Harga Pasar Dalam Islam - Zia Ulhaq , Muhamad ; Achiria, Siti (Department of Islamic Economic Law, Institut Agama Islam (IAI) Al-Qolam, 2018)
The market has a very important role in the economy. Islam recognizes the existence of market mechanisms if the market runs perfectly. The problem that often occurs is the distortion in the market that impedes the economy, so Islam considers the need for government intervention in price-fixing. This paper aims to find out the concept of Ibn Taimiyah's thoughts regarding the regulation of market prices in Islam. The method used is library research using descriptive analysis method. One of Thought Economy Ibn Taimiyah explained that the price was determined by the strength of demand and supply. If the price increase is due to fraud and the inequality of the market mechanism, the government must implement a policy in determining prices. If there is a natural price increase, the government does not have the authority to set prices. Therefore, the thought of Ibn Taimiyah provides an understanding of what happened in the past but can be expected for the present state of life of the people.